2014
DOI: 10.1017/s0025315413001793
|View full text |Cite
|
Sign up to set email alerts
|

Molecular data on the genusOkenia(Nudibranchia: Goniodorididae) reveal a new cryptic species from New South Wales (Australia)

Abstract: Preliminary molecular data obtained from one mitochondrial (COI) and one nuclear marker (H3) from the available species of the genus Okenia have revealed a new cryptic species of this genus. The new species (Okenia harastii sp. nov.), from New South Wales (NSW) eastern Australia, has a light brown body with scattered dark brown and white spots of different sizes, and six pairs of translucent mantle processes. Okenia harastii sp. nov. is compared with other Okenia species from NSW and with other morphologically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
12

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 22 publications
0
23
0
12
Order By: Relevance
“…In fact, T. divae was not included in Pola et al (2007Pola et al ( , 2008 because the specimens were missing, but it is included in Pola et al (2014a) and it clusters together with T. limaciformis and T. amakusana. Molecular sequences for several genes are still missing for some species such as T. blacki, but the morphological and molecular analyses so far clearly show that T. limaciformis, T. amakusana and T. divae are grouped together and well as are T. abdere and T. blacki.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, T. divae was not included in Pola et al (2007Pola et al ( , 2008 because the specimens were missing, but it is included in Pola et al (2014a) and it clusters together with T. limaciformis and T. amakusana. Molecular sequences for several genes are still missing for some species such as T. blacki, but the morphological and molecular analyses so far clearly show that T. limaciformis, T. amakusana and T. divae are grouped together and well as are T. abdere and T. blacki.…”
Section: Discussionmentioning
confidence: 99%
“…When including COI sequence for T. mediterranea sp. nov. in the molecular dataset of Pola et al (2014a), T. mediterranea sp. nov. clusters together with maximum support (PP = 1.00) with T. limaciformis, T. amakusana and T. divae (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carmona et al 2011;Ornelas-Gatdula et al 2011;Pola et al 2012;Pola et al 2014;Matsuda & Gosliner 2017), whereas species treated earlier as different taxa are simply colour variants of the same species (e.g. Pola et al 2006b;Padula et al 2016).…”
Section: Final Considerationsmentioning
confidence: 99%
“…A recent paper by Pola et al (2014) compares specimens of a new species of the genus from Australia (Okenia harastii Pola, Roldán and Padilla, 2014) with the specimens of Okenia zoobotryon originally described by Smallwood (1910Smallwood ( , 1912 but also with specimens recently collected in Bermuda. Pola et al (2014) showed that although both species are initially very similar they could be distinguished by morphological and molecular data.…”
mentioning
confidence: 99%